Multi-layer coating structure with double-reinforced inlaying effect and ultraviolet shielding effect
By introducing the inlay structure of nanoparticles and magnetron sputtering metal layers into the UV cured coating, the problem of insufficient bonding between layers in the prior art is solved, strong bonding and ultraviolet shielding are achieved, and the light resistance of the coating is improved. Aging performance and environmental protection advantages.
Patent Information
- Application Number
- CN202411198728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
At this stage, UV curing coatings have shortcomings in improving the bonding force between the primer layer and the magnetron sputtered metal layer and the magnetron sputtered metal layer and the topcoat layer, which affects the protective performance and photoaging resistance of the coating.
Using a multi-layer coating design from bottom to top structure, including substrate, UV cured primer layer with nanoparticles modified and magnetron sputtered metal layer, and UV cured topcoat layer with nanoparticles modified and two All of them are concave and convex structures to achieve mosaic occlusion, enhance interlayer binding force, and reduce their absorption through the shielding effect of nanoparticles on ultraviolet rays.
Achieve a strong combination of primer layer, magnetron sputtered metal layer, magnetron sputtered metal layer and topcoat layer, improve the photo-aging resistance and ultraviolet shielding ability of the coating, and has emission reduction, energy saving, carbon reduction, etc. Environmental protection advantages.
Smart Images

Figure CN119119544A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective coatings, and relates to a multi-layer coating structure with dual enhanced embedding effect and ultraviolet shielding effect. Background Art
[0002] UV curing refers to the process of photoinitiators absorbing UV radiation to initiate photopolymerization, which cures the monomers and oligomers in the coating into films. Due to its short curing time, high efficiency, and the small amount of solvent required during production and use, it has many advantages such as "emission reduction", "energy saving", and "efficiency improvement", which is in line with the global green economic development route of reducing pollution and carbon emissions.
[0003] As a protective coating, the failure of UV-curing coating is related to the absorption of ultraviolet rays by polymers. On the one hand, reducing the effective absorption of ultraviolet rays by polymers will help improve the protective ability of UV-curing coatings; on the other hand, the interlayer bonding strength of multi-layer coatings plays an important role in enhancing the protective ability (anti-light aging ability). At present, improving the interlayer bonding strength mainly relies on the pre-treatment of the substrate to reduce the impact of impurities on the coating quality and bonding strength, so as to achieve a close bond between the primer layer and the substrate. However, there is still a lack of methods to strengthen the bonding between the primer layer and the magnetron sputtered metal layer, and the bonding between the magnetron sputtered metal layer and the topcoat layer. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a multi-layer coating structure with dual enhanced embedding effect and UV shielding effect.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] 1. A multilayer coating structure with dual enhanced inlay effect and UV shielding effect, the multilayer coating structure comprising, from bottom to top, a substrate, a UV-curing primer layer modified with nanoparticles, a magnetron sputtering metal layer, and a UV-curing topcoat layer modified with nanoparticles;
[0007] The UV-cured primer layer modified with nanoparticles and the magnetron sputtered metal layer both have a concave-convex structure, and the two can be inlaid and engaged with each other;
[0008] The nanoparticle-modified UV-cured topcoat layer and the magnetron sputtering metal layer both have concave-convex structures, and the two can be inlaid and engaged with each other.
[0009] Preferably, the UV-curable primer layer modified with nanoparticles is prepared according to the following method: adding nanoparticles to a UV-curable primer coating, spraying the mixture on the upper surface of the substrate after uniform mixing, and curing the mixture after baking to obtain a UV-curable primer layer modified with nanoparticles;
[0010] The amount of nanoparticles added in the UV curing primer layer is 1 wt.% to 15 wt.%.
[0011] Further preferably, the curing after baking is specifically: baking at 45°C to 70°C for 100s to 200s, and then 2 ~900mJ / cm 2 energy solidification.
[0012] Further preferably, the nanoparticles are prepared according to the following method: a coupling agent is added to a mixed solvent with a pH of 3 to 5 for hydrolysis, and after adding a nanoparticle masterbatch, a modification treatment is performed at 70 to 110° C. for 200 to 300 minutes to obtain nanoparticles, wherein the mass ratio of the coupling agent to the nanoparticle masterbatch is 1:3 to 8, and the mixed solvent is obtained by mixing anhydrous ethanol and water in a volume ratio of 3:1;
[0013] The coupling agent includes any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrichlorosilane or vinyltriacetylsilane;
[0014] The nanoparticle masterbatch is any one or more of nano titanium dioxide, nano zinc oxide, nano silicon dioxide, nano ferric oxide, nano graphene, nano cerium dioxide, nano ferric oxyhydroxide, nano zirconium dioxide, nano aluminum oxide or nano magnesium oxide.
[0015] Preferably, the metal in the magnetron sputtering metal layer is any one of aluminum, aluminum alloy, chromium or chromium alloy.
[0016] Preferably, the UV-curable topcoat layer modified with nanoparticles is prepared according to the following method: adding nanoparticles to a UV-curable topcoat coating, spraying the mixture on the upper surface of the magnetron sputtered metal layer after uniform mixing, and curing the mixture after baking to obtain a UV-curable topcoat layer modified with nanoparticles;
[0017] The amount of nanoparticles added in the nanoparticle-modified UV-curing topcoat layer is 1 wt.% to 15 wt.%.
[0018] Further preferably, the nanoparticles are prepared according to the following method: a coupling agent is added to a mixed solvent with a pH of 3 to 5 for hydrolysis, and after adding a nanoparticle masterbatch, a modification treatment is performed at 70 to 110° C. for 200 to 300 minutes to obtain nanoparticles, wherein the mass ratio of the coupling agent to the nanoparticle masterbatch is 1:3 to 8, and the mixed solvent is obtained by mixing anhydrous ethanol and water in a volume ratio of 3:1;
[0019] The coupling agent includes any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrichlorosilane or vinyltriacetylsilane;
[0020] The nanoparticle masterbatch includes any one or more of materials such as nano titanium dioxide, nano zinc oxide, nano silicon dioxide, nano ferric oxide, nano graphene, nano cerium dioxide, nano hydroxy iron oxide, nano zirconium dioxide, nano aluminum oxide or nano magnesium oxide.
[0021] More preferably, the curing after baking is specifically: baking at 45°C to 70°C for 100s to 200s, and then 2 ~1200mJ / cm 2 energy solidification.
[0022] Preferably, the primer material in the UV-curable primer layer modified with nanoparticles and the topcoat material in the UV-curable topcoat layer modified with nanoparticles are matching models from the same manufacturer.
[0023] Preferably, the substrate is any one of polyethylene (PE), polyvinyl chloride (PVC), polystyrene (PS), polypropylene (PP) or ABS resin.
[0024] The beneficial effects of the present invention are as follows: the present invention discloses a multi-layer coating structure with dual enhanced inlay effect and ultraviolet shielding effect, which comprises, from bottom to top, a substrate, a UV-curing primer layer modified with nanoparticles, a magnetron sputtering metal layer and a UV-curing topcoat layer modified with nanoparticles, and has the following advantages: (1) in the multi-layer coating structure provided by the present invention, nanoparticles are added to the primer layer, and a concave-convex morphology is formed on the contact surface with the magnetron sputtering metal layer, and the primer layer and the magnetron sputtering metal layer are mutually inlaid and interlocked, thereby realizing a strong bond between the primer layer and the magnetron sputtering metal layer; (2) in the multi-layer coating structure provided by the present invention, the magnetron sputtering metal layer replicates the surface concave-convex morphology of the primer layer, and mutually interlocks with the topcoat layer. Inlay bite, realize the strong bonding between the magnetron sputtering metal layer and the topcoat layer; (3) Nanoparticles are added to the topcoat layer in the multilayer coating structure provided by the present invention, so that the coating has a shielding effect on ultraviolet rays, and the coating is not easily damaged by ultraviolet rays; (4) The UV-curing primer layer modified with nanoparticles and the UV-curing topcoat layer modified with nanoparticles provided by the present invention both contain organic-inorganic hybrid bonding, forming an organic-inorganic hybrid cross-linking structure, and the resin and inorganic nanoparticles are bonded to strengthen the coating and improve the comprehensive performance of the coating; (5) The multilayer coating structure provided by the present invention has excellent light aging resistance due to its shielding effect on ultraviolet rays and good interlayer bonding force. In addition, the multilayer coating structure provided by the present invention has the advantages of emission reduction, energy saving, and carbon reduction. Through the inlay effect, the interlayer bonding between the primer layer and the magnetron sputtering metal layer, and the interlayer bonding between the magnetron sputtering metal layer and the topcoat layer can be strengthened; through the reflection and absorption of ultraviolet rays by nanoparticles, the shielding ability of the multilayer coating structure to ultraviolet rays is improved, and the absorption of ultraviolet rays by polymers is reduced. This coating has environmental advantages such as energy saving and emission reduction. It can fill the gaps in existing technologies in this field and improve the coating's anti-light aging performance.
[0025] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0027] Figure 1 Schematic diagram of the structure of the multilayer coating with dual enhanced embedding effect and ultraviolet shielding effect provided by the present invention, wherein 1 is a substrate, 2 is a UV-curing primer layer modified with nanoparticles, 3 is a magnetron sputtering metal layer, and 4 is a UV-curing topcoat layer modified with nanoparticles;
[0028] Figure 2 It is a schematic diagram of the organic-inorganic hybrid crosslinking structure provided by the present invention. DETAILED DESCRIPTION
[0029] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0030] The nanoparticles used in the following examples are nanoparticles modified with γ-methacryloxypropyltrimethoxysilane, as shown in "Surface Modification of Nano-SiO2 by Silane Coupling Agent KH570 and Its Dispersion Stability" (Su Ruicai, Li Wenfang, Peng Jihua, Du Jun, Chemical Industry Progress, Vol. 28, No. 9, 2009, 1596), and the specific preparation method is as follows:
[0031] (1) Weigh 30 g of γ-methacryloxypropyltrimethoxysilane, dissolve it in a mixture of anhydrous ethanol and deionized water in a volume ratio of 3:1, adjust the pH to between 3 and 4, and fully hydrolyze;
[0032] (2) Weigh 100 g of nanoparticles, add fully hydrolyzed γ-methacryloxypropyltrimethoxysilane solvent, and react at 80° C. for 240 min;
[0033] (3) After the reaction is completed, the suspension is centrifuged and purified, and after drying and refining, nanoparticles modified with γ-methacryloxypropyltrimethoxysilane are obtained.
[0034] Nano-titanium dioxide is used as the nano-mother particle in the above step (2) to prepare the nano-particles used in the following Example 1; nano-zinc oxide is used as the nano-mother particle in the above step (2) to prepare the nano-particles used in the following Examples 2 and 3.
[0035] The NNP primer used in the following examples is Bonfort BSJ-7170, and the NNP topcoat is Bonfort BSJ-7213.
[0036] Comparative Example 1
[0037] The comparative example provides a multi-layer coating structure without mosaic effect and UV shielding effect, and its composition is shown in Table 1.
[0038] Table 1 Composition of the multilayer coating structure in Comparative Example 1
[0039] UV curing primer layer NNP Primer Magnetron sputtering metal layer Aluminum Target UV curing topcoat NNP Topcoat
[0040] The preparation method of the above-mentioned multi-layer coating structure without mosaic effect and UV shielding effect is as follows:
[0041] (1) Primer layer spray curing: 100g UV curing primer coating (NNP primer) was sprayed on the upper surface of the ABS resin substrate with a spray gun, baked at 45℃~70℃ for 100s, and then heated at 600mJ / cm 2 ~800mJ / cm 2 The UV-curing primer layer can be obtained by curing within the energy range;
[0042] (2) Metal layer sputtering: The magnetron sputtering metal layer (aluminum target) is sputtered on the upper surface of the UV-curing primer layer modified with nanoparticles at a power in the range of 10 to 15 kW to form a magnetron sputtering metal layer;
[0043] (3) Topcoat spray curing: 100 g of UV curing topcoat (NNP topcoat) was sprayed on the upper surface of the magnetron sputtered metal layer using a spray gun, and then baked at 45°C to 70°C for 100 s and heated at 600 mJ / cm 2 ~800mJ / cm 2 The UV-curing topcoat layer can be obtained by curing within the energy range.
[0044] Example 1
[0045] A multi-layer coating structure with enhanced embedding effect and UV shielding effect, the composition of which is specifically shown in Table 2.
[0046] Table 2 Composition of the multilayer coating structure in Example 1
[0047] Contains nanoparticle-modified UV-curable primer layer NNP Primer + 1.00wt.% Nanoparticles Magnetron sputtering metal layer Aluminum Target UV-curable topcoat layer modified with nanoparticles NNP topcoat + 4.00wt.% nanoparticles
[0048] The preparation method of the multi-layer coating structure with dual enhanced embedding effect and UV shielding effect is as follows:
[0049] (1) Primer layer spray curing: 99g NNP primer and 1g nanoparticles were mixed evenly, sprayed on the upper surface of the ABS resin substrate with a spray gun, and baked (baking temperature 45℃~70℃, baking leveling time 100s), and then used 700mJ / cm 2 ~900mJ / cm 2 The UV-curing primer layer containing nanoparticles can be obtained by UV-curing with energy of
[0050] (2) Sputtering of metal layer: sputtering metal aluminum onto the upper surface of the UV-curable primer layer modified with nanoparticles at a power in the range of 10 to 15 kW to obtain a magnetron sputtered metal layer;
[0051] (3) Topcoat spray curing: 96 g NNP topcoat and 4 g nanoparticles were mixed evenly, sprayed on the upper surface of the magnetron sputtered metal layer with a spray gun, and baked (baking temperature 45°C to 70°C, baking leveling time 100 s), and then 1000 mJ / cm 2 ~1200mJ / cm 2 The UV-curing topcoat layer modified with nanoparticles can be obtained by UV-curing the surface of the nanoparticles.
[0052] Example 2
[0053] A multi-layer coating structure with enhanced embedding effect and UV shielding effect, the composition of which is specifically shown in Table 3.
[0054] Table 3 Composition of the multilayer coating structure in Example 1
[0055] Contains nanoparticle-modified UV-curable primer layer NNP Primer + 2.5wt.% Nanoparticles Magnetron sputtering metal layer Aluminum Target UV-curable topcoat layer modified with nanoparticles NNP topcoat + 3.5wt.% nanoparticles
[0056] The preparation method of the multi-layer coating structure with dual enhanced embedding effect and UV shielding effect is as follows:
[0057] (1) Primer layer spray curing: 97.5 g NNP primer and 2.5 g nanoparticles were mixed evenly, sprayed on the upper surface of the ABS resin substrate with a spray gun, and baked (baking temperature 45°C to 70°C, baking leveling time 200 s), and then used 700 mJ / cm 2 ~900mJ / cm 2 The UV-curing primer layer containing nanoparticles can be obtained by UV-curing with energy of
[0058] (2) Sputtering of metal layer: sputtering metal aluminum onto the upper surface of the UV-curable primer layer modified with nanoparticles at a power in the range of 10 to 15 kW to obtain a magnetron sputtered metal layer;
[0059] (3) Topcoat spray curing: 96.5 g NNP topcoat and 3.5 g nanoparticles were mixed evenly, sprayed on the upper surface of the magnetron sputtered metal layer with a spray gun, and baked (baking temperature 45°C to 70°C, baking leveling time 200 s), and then 1000 mJ / cm 2 ~1200mJ / cm 2 The UV-curing topcoat layer modified with nanoparticles can be obtained by UV-curing the surface of the nanoparticles.
[0060] Example 3
[0061] A multi-layer coating structure with enhanced embedding effect and UV shielding effect, the composition of which is specifically shown in Table 4.
[0062] Table 4 Composition of the multilayer coating structure in Example 1
[0063] Contains UV-curable primer layer modified with nanoparticles NNP Primer + 3.5wt.% Nanoparticles Magnetron sputtering metal layer Aluminum Target UV-curable topcoat layer modified with nanoparticles NNP topcoat + 3.5wt.% nanoparticles
[0064] The preparation method of the multi-layer coating structure with dual enhanced embedding effect and UV shielding effect is as follows:
[0065] (1) Primer layer spray curing: 96.5 g NNP primer and 3.5 g nanoparticles were mixed evenly, sprayed on the upper surface of the ABS resin substrate with a spray gun, and baked (baking temperature 45°C to 70°C, baking leveling time 100 s), and then UV curing energy 700 mJ / cm 2 ~900mJ / cm 2 A UV-curable primer layer modified with nanoparticles can be obtained;
[0066] (2) Sputtering of metal layer: sputtering metal aluminum onto the upper surface of the UV-curable primer layer modified with nanoparticles at a power in the range of 10 to 15 kW to obtain a magnetron sputtered metal layer;
[0067] (3) Topcoat spray curing: 96.5 g NNP topcoat and 3.5 g nanoparticles were mixed evenly, sprayed on the upper surface of the magnetron sputtered metal layer with a spray gun, and baked (baking temperature 45°C to 70°C, baking leveling time 100 s), and then 1000 mJ / cm 2 ~1200mJ / cm 2 The UV-curing topcoat layer modified with nanoparticles can be obtained by UV-curing the surface of the nanoparticles.
[0068] Figure 1 Schematic diagram of the multi-layer coating structure with inlay effect and UV shielding effect of the present invention, wherein 1 is a substrate, 2 is a UV-curing primer layer modified with nanoparticles, 3 is a magnetron sputtering metal layer, and 4 is a UV-curing topcoat layer modified with nanoparticles. Figure 1 It can be seen that the multilayer coating structure with inlay effect and UV shielding effect of the present invention comprises, from bottom to top, a substrate, a UV-curing primer layer modified with nanoparticles, a magnetron sputtering metal layer and a UV-curing topcoat layer modified with nanoparticles.
[0069] Figure 2 Schematic diagram of the organic-inorganic hybrid crosslinking structure provided by the present invention. Figure 2It can be seen that the modified nanoparticles are introduced into the photosensitive groups (groups containing unsaturated bonds) in the coating to participate in bonding, forming more stable covalent bonds, and bonding between the resin and the inorganic nanoparticles to strengthen the coating and improve the overall performance of the coating. According to Pauling's hybrid orbital theory, "bonding" is the cause and driving force of atomic orbital hybridization, and orbital hybridization only occurs during the bonding process. Therefore, orbital hybridization of nanoparticles, active monomers and prepolymers occurs inside the coating, and the electron clouds overlap, reducing the energy of the system, making it more stable and more weather-resistant.
[0070] The multilayer coating structure without mosaic effect and UV shielding effect in the above-mentioned comparative example 1 and the multilayer coating structure with enhanced mosaic effect and UV shielding effect in Examples 1 to 3 were subjected to performance tests. The performance test methods are as follows: (1) Adhesion: The adhesion test adopts the cross-cutting method. After the sample is placed for more than six hours, a hundred grids are cut according to the ISO 2409 standard. The grid lines in the same direction must be parallel to each other, and the grid lines in different directions must be perpendicular to each other to form a grid pattern. Use 3M adhesive tape to flatten and press the cross-cutting area, and use an angle of about 60° to smoothly tear off the tape within 0.5 seconds to 1 second. Each test piece must be tested at least three different positions. (2) Pencil hardness: The pencil hardness test refers to GB / T 6739-2022. This is a method for measuring the hardness of a coating by pushing a pencil of known hardness on the coating. It tests the ability of the coating surface to resist scratches or other defects. The main principle is: use a pencil lead of a specified geometric shape to press down on the coating surface at a 45° angle under a load of (7.35±0.15)N, and measure the pencil hardness of the coating by pushing the pencil on the coating; gradually increase the hardness of the pencil until visible defects appear on the surface, and the hardness of the hardest pencil that does not cause defects on the coating surface represents the pencil hardness of the coating. (3) Light aging resistance: According to the test method specified in GB / T 1865-2009, the sample wetting cycle is continuously operated according to the cycle A mode in 9.5. After every 100 hours of the test time, take out the sample and conduct a visual inspection to determine whether the test sample has new defects such as cracks, spots, deformation, blistering and peeling that affect the appearance quality of the product. Three samples are tested under each working condition, and the weighted average is taken as the effective protection time of the coating. The specific test results are shown in Table 5.
[0071] Table 5 Adhesion, pencil hardness and light aging test results
[0072]
[0073] In summary, the present invention discloses a multilayer coating structure with dual enhanced inlay effect and UV shielding effect, which comprises, from bottom to top, a substrate, a UV-curing primer layer modified with nanoparticles, a magnetron sputtering metal layer, and a UV-curing topcoat layer modified with nanoparticles, and has the following advantages: (1) In the multilayer coating structure provided by the present invention, nanoparticles are added to the primer layer, and a concave-convex morphology is formed on the contact surface with the magnetron sputtering metal layer, and the primer layer and the magnetron sputtering metal layer are inlaid and interlocked with each other, so as to achieve a strong bond between the primer layer and the magnetron sputtering metal layer; (2) In the multilayer coating structure provided by the present invention, the magnetron sputtering metal layer replicates the surface concave-convex morphology of the primer layer, and the surface The paint layers are interlocked and interlocked with each other to achieve a strong bond between the magnetron sputtering metal layer and the topcoat layer; (3) Nanoparticles are added to the topcoat layer in the multilayer coating structure provided by the present invention, so that the coating has a shielding effect on ultraviolet rays, and the coating is not easily damaged by ultraviolet rays; (4) The UV-curing primer layer modified with nanoparticles and the UV-curing topcoat layer modified with nanoparticles provided by the present invention both contain organic-inorganic hybrid bonds, and the resin and inorganic nanoparticles are bonded to strengthen the coating and improve the comprehensive performance of the coating; (5) The multilayer coating structure provided by the present invention has excellent light aging resistance due to its shielding effect on ultraviolet rays and good interlayer bonding. In addition, the multilayer coating structure provided by the present invention has the advantages of emission reduction, energy saving, and carbon reduction. Through the inlay effect, the interlayer bonding between the primer layer and the magnetron sputtering metal layer, and the interlayer bonding between the magnetron sputtering metal layer and the topcoat layer can be strengthened; through the reflection and absorption of ultraviolet rays by nanoparticles, the shielding ability of the multilayer coating structure to ultraviolet rays is improved, and the absorption of ultraviolet rays by polymers is reduced. This coating has environmental advantages such as energy saving and emission reduction. It can fill the gaps in existing technologies in this field and improve the coating's anti-light aging performance.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A multi-layer coating structure with dual enhanced embedding effect and UV shielding effect, characterized in that: The multi-layer coating structure comprises, from bottom to top, a substrate, a UV-curing primer layer modified with nanoparticles, a magnetron sputtering metal layer, and a UV-curing topcoat layer modified with nanoparticles; The UV-cured primer layer modified with nanoparticles and the magnetron sputtered metal layer both have a concave-convex structure, and the two can be inlaid and engaged with each other; The nanoparticle-modified UV-cured topcoat layer and the magnetron sputtering metal layer both have concave-convex structures, and the two can be inlaid and engaged with each other.
2. The multi-layer coating structure according to claim 1, characterized in that: The UV-curable primer layer modified with nanoparticles is prepared according to the following method: nanoparticles are added to a UV-curable primer coating, mixed evenly and then sprayed on the upper surface of the substrate, and then cured by baking to obtain a UV-curable primer layer modified with nanoparticles; The amount of nanoparticles added in the UV curing primer layer is 1 wt.% to 15 wt.%.
3. The multi-layer coating structure according to claim 2, characterized in that: The post-baking curing is specifically as follows: baking at 45°C to 70°C for 100s to 200s, and then 2 ~900mJ / cm 2 energy solidification.
4. The multi-layer coating structure according to claim 2, characterized in that: The nanoparticles are prepared according to the following method: a coupling agent is added to a mixed solvent with a pH of 3 to 5 for hydrolysis, and a nanoparticle masterbatch is added and then subjected to a modification treatment at 70 to 110° C. for 200 to 300 minutes to obtain nanoparticles, wherein the mass ratio of the coupling agent to the nanoparticle masterbatch is 1:3 to 8, and the mixed solvent is obtained by mixing anhydrous ethanol and water in a volume ratio of 3:1; The coupling agent includes any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrichlorosilane or vinyltriacetylsilane; The nanoparticle masterbatch is any one or more of nano titanium dioxide, nano zinc oxide, nano silicon dioxide, nano ferric oxide, nano graphene, nano cerium dioxide, nano ferric oxyhydroxide, nano zirconium dioxide, nano aluminum oxide or nano magnesium oxide.
5. The multi-layer coating structure according to claim 1, characterized in that: The metal in the magnetron sputtering metal layer is any one of aluminum, aluminum alloy, chromium or chromium alloy.
6. The multi-layer coating structure according to claim 1, characterized in that: The UV-curable topcoat layer modified with nanoparticles is prepared according to the following method: adding nanoparticles to a UV-curable topcoat coating, spraying the nanoparticles onto the upper surface of the magnetron sputtering metal layer after mixing evenly, and curing the nanoparticle-modified UV-curable topcoat layer after baking; The amount of nanoparticles added in the nanoparticle-modified UV-curing topcoat layer is 1 wt.% to 15 wt.%.
7. The multi-layer coating structure according to claim 6, characterized in that: The nanoparticles are prepared according to the following method: a coupling agent is added to a mixed solvent with a pH of 3 to 5 for hydrolysis, and a nanoparticle masterbatch is added and then subjected to a modification treatment at 70 to 110° C. for 200 to 300 minutes to obtain nanoparticles, wherein the mass ratio of the coupling agent to the nanoparticle masterbatch is 1:3 to 8, and the mixed solvent is obtained by mixing anhydrous ethanol and water in a volume ratio of 3:1; The coupling agent includes any one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrichlorosilane or vinyltriacetylsilane; The nanoparticle masterbatch includes any one or more of materials such as nano titanium dioxide, nano zinc oxide, nano silicon dioxide, nano ferric oxide, nano graphene, nano cerium dioxide, nano hydroxy iron oxide, nano zirconium dioxide, nano aluminum oxide or nano magnesium oxide.
8. The multi-layer coating structure according to claim 6, characterized in that: The post-baking curing is specifically: baking at 45°C to 70°C for 100s to 200s, and then 2 ~1200mJ / cm 2 energy solidification.
9. The multi-layer coating structure according to claim 1, characterized in that: The primer material in the UV-curing primer layer modified with nanoparticles and the topcoat material in the UV-curing topcoat layer modified with nanoparticles are matching models from the same manufacturer.
10. The multi-layer coating structure according to claim 1, characterized in that: The substrate is any one of polyethylene, polyvinyl chloride, polystyrene, polypropylene or ABS resin.
